Development of magnetic flux leakage technique for examination of steam generator tubes of prototype fast breeder reactor. (September 2015) - Singh, W. Sharatchandra; Rao, B. Purnachandra; Thirunavukkarasu, S.; Mahadevan, S.; Mukhopadhyay, C.K.; Jayakumar, T.
Highlights: For non-destructive detection of small localized defects in SG tubes of PFBR, tandem GMR array sensors based MFL technique developed. 3D-finite element modeling performed for optimization of magnetizing current and spacing between the magnetizing coils. The optimized magnetizing structure with ferrite core and guides detected 0.54 mm deep OD circumferential notch, 0.56 mm deep flat bottom hole, and 1.08 mm diameter hole in the tube with a SNR better than 6 dB. Images of notches have been obtained using the tandem GMR array sensor. The use of MFL and remote field eddy current techniques is expected to ensure comprehensive inspection of SG tubes of PFBR. Abstract: For non-destructive examination of small diameter (outer diameter, OD 17.2 mm) and thick walled (wall thickness, 2.3 mm) ferromagnetic Modified 9Cr–1Mo steel steam generator (SG) tubes of Prototype Fast Breeder Reactor (PFBR), this paper proposes magnetic flux leakage (MFL) technique. Three dimensional finite element (3D-FE) modeling has been performed to optimize the magnetizing unit and inter-coil spacing of bobbin coils used for axial magnetization of the tube. The performance of the technique has been evaluated experimentally by measuring the axial ( Ba ) component of the leakage fields from localized machined defects in SG tubes. The MFL technique has shown capability to detect and image tube outside defects with a signal-to-noise ratio (SNR) better than 6 dB. Study reveals that Inconel support plates surrounding the SG tubes do not influence the MFL signals. As the MFL technique can detect localized defects in the presence of support plates as well as sodium and the remote field eddy current technique is sensitive to distributed wall thinning, their combined use will ensure comprehensive inspection of the SG tubes.